Oral administration of curcumin and quercetin nanoparticles can improve ulcerative colitis by regulating intestinal microorganisms - Li, Yingxi; Xu, Zhiyue; Zhao, Shiyang; Huang, Tianyi; Xu, Jianzhong; Wang, Sitong; Sang, Yaxin; Yu, Wenlong; Wang, Xianghong (Frontiers in Nutrition, 2025)
BackgroundCurcumin has been proved to relieve ulcerative colitis (UC). However, the premature release of gastrointestinal tract will lead to insufficient accumulation of curcumin in colon and affect the improvement effect. Therefore, we developed a kind of oral nanoparticles (Zein-CS-Cur-Que), which made quercetin promote the absorption of curcumin in colon by efflux carrier and inhibiting metabolic enzymes, and at the same time encapsulated curcumin and quercetin with zein and sodium caseinate to promote the targeted release in colon.Methods3.5% dextran sodium sulfate was used to establish ulcerative colitis (UC) model in mice, and the improvement effect of nanoparticles on ulcerative colitis was evaluated by comprehensive basic score (weight change rate, DAI score, liver index, and spleen index), inflammatory factors (TNF-α, IL-1β, IL-6, IL-10, and IFN-γ) and oxidative stress (MDA, SOD, CAT, and MPO). The intestinal flora was sequenced by 16S rRNA, and the secretion of short-chain fatty acids was determined by GC-MS. Immunohistochemistry (ZO-1, Claudin-1, and Occludin) and real-time quantitative reverse transcription PCR (qRT-PCR) (TLR4/NF-κB and JAK2/STAT3) were used to analyze the expression of related genes.ResultsThe results showed that Zein-CS-Cur-Que can reduce pro-inflammatory factors (INF-γ, IL-6, IL-1β, and TNF-α), increase anti-inflammatory factor (IL-10), up-regulate the expression level of tight junction proteins (ZO-1, Claudin-1, and Occludin) to restore the intestinal barrier, and down-regulate the expression of related protein genes in TLR4/NF-κB and JAK2/STAT3. Ultimately, modulating the relative abundance of Firmicutes and Bacteroidetes promotes the production of short-chain fatty acids and reverses the damage caused by ulcerative colitis.ConclusionNanoparticles (Zein-CS-Cur-Que) can significantly reduce inflammatory reaction, restore intestinal barrier, regulate the expression of related protein genes in TLR4/NF-κB and JAK2/STAT3 pathways, and significantly improve ulcerative colitis. Furthermore, the construction of Zein-CS-Cur-Que provides a scientific basis for increasing curcumin targeting and ameliorating ulcerative colitis.